Ethics of Storytelling: The Wounds of Deception and Pseudo-PTSD in Atonement - Harith Ismael Turki; Merve Feryal Ashmawy (Nalans)
Ian McEwan’s Atonement (2001) is one of the most controversial novels due to the complexity of its narratives and characters, particularly its central character. Therefore, this article deals with pseudo-PTSD in Atonement, examining how trauma is delineated, built, and manipulated within the metafictional framework of the novel. While classical PTSD is depicted through forced memories of traumatic events, McEwan’s protagonist produces an unreliable narrative of guilt and redemption that parodies trauma without genuine experience. This study explores the character’s psychological state, arguing that her self-imposed suffering functions as a simulacrum of PTSD—what can be termed pseudo-PTSD—a term coined by Rosen & Tylor (2007). Drawing their perspective, the article examines Briony’s retrospective storytelling as both a coping mechanism and an act of self-mythologization, highlighting the ethical and epistemological implications of traumatised narrator, narrating trauma and traumatic narrative. Ultimately, Atonement challenges the reliability of memory and the legitimacy of self-inflicted psychological ‘wounds’, raising critical questions about authorship, responsibility, and the commodification of suffering in fiction.